Jesus becoming Jesus. Prologue and the Book of Signs - Weinandy, Thomas G. (Thomas Gerard) (The Catholic University of America Press, 2021)
Jesus Becoming Jesus, Volume 2: A Theological Interpretation of the Gospel of John: Prologue and the Book of Signs follows upon the first volume of this series entitled Jesus Becoming Jesus. The first volume was a theological interpretation of the Gospels of Matthew, Mark and Luke. Unlike many conventional biblical commentaries, Weinandy concentrates on the theological content contained within John's Gospel. He does this in the light of the Church's doctrinal and theological tradition, particularly in keeping with the Second Vatican Council's Dogmatic Constitution, Dei Verbum. This is accomplished through a close reading of John's Gospel, theologically interpreting each chapter of the Gospel sequentially. In so doing he also takes into account the Johannine corpus as a whole. He also relates John's Gospel to relevant material found within the Synoptic Gospels, the Pauline Corpus and other New Testament writings. This original theological interpretation focuses primarily on the intertwining theological themes contained within John's Gospel, specifically within the Prologue and the Book of Signs - light and darkness, the seven miracle-signs, the sacraments of baptism and the Eucharist, the seven "I Am" sayings, the contentious dialogues with the Jews, Jesus' relationship to his Father as the Father's incarnate Word and Son, etc. Within all of these interlocking themes one finds the importance of Jesus' saving actions - the salvific works of his Father. The overarching theme of this book, as the title suggests, is that Jesus, being named Jesus, throughout his public ministry is enacting his name and so becoming who he is - YHWH-Saves. Weinandy offers a singular, vibrant, and luminous reading of John's Gospel; one that reveals the Evangelist's theological depth and doctrinal sophistication. In so doing, Weinandy makes manifest the particular beauty of the Gospel According to John